2012
DOI: 10.1089/scd.2011.0630
|View full text |Cite
|
Sign up to set email alerts
|

Interordinal Chimera Formation Between Medaka and Zebrafish for Analyzing Stem Cell Differentiation

Abstract: Chimera formation is a standard test for pluripotency of stem cells in vivo. Interspecific chimera formation between distantly related organisms offers also an attractive approach for propagating endangered species. Parameters influencing interspecies chimera formation have remained poorly elucidated. Here, we report interordinal chimera formation between medaka and zebrafish, which separated ∼320 million years ago and exhibit a more than 2-fold difference in developmental speed. We show that, on transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 45 publications
0
29
0
1
Order By: Relevance
“…The ability of diploid medaka ES cell line to form chimerism in the ZES1-injected embryos further corroborates with the earlier finding reporting the ability of this cell line to embrace the zebrafish developmental program. 29 We demonstrated that F 1 germline chimeras could be generated by the transplantation of GFP-ZES1 cells, which overexpressed GFP under the influence of the CMV promoter, into recipient zebrafish embryos. The transplanted GFP-ZES1 cells contributed to normal embryonic development of the recipient embryos, with GFP expression detected in regions such as the brain, eye, epidermis, fin, and heart.…”
Section: Cellsmentioning
confidence: 95%
See 2 more Smart Citations
“…The ability of diploid medaka ES cell line to form chimerism in the ZES1-injected embryos further corroborates with the earlier finding reporting the ability of this cell line to embrace the zebrafish developmental program. 29 We demonstrated that F 1 germline chimeras could be generated by the transplantation of GFP-ZES1 cells, which overexpressed GFP under the influence of the CMV promoter, into recipient zebrafish embryos. The transplanted GFP-ZES1 cells contributed to normal embryonic development of the recipient embryos, with GFP expression detected in regions such as the brain, eye, epidermis, fin, and heart.…”
Section: Cellsmentioning
confidence: 95%
“…29,30 Labeled ZES1 and MES1 cells were suspended in transplantation medium (TM; 100 mM NaCl, 5 mM KCl, 5 mM HEPES, pH 7.1). Zebrafish embryos were treated for 2 min with pronase E (1 mg/mL; Sigma) at 26°C for dechorionation.…”
Section: Embryonic Stem Cell Feeder-free Pluripotencymentioning
confidence: 99%
See 1 more Smart Citation
“…Observation and photography was carried out on Leica MZFIII stereomicroscope, Zeiss Axiovert invert and Axiovert upright microscopes with a Zeiss AxioCam M5Rc digital camera (Zeiss Corp., Germany) as described previously [44,45].…”
Section: Microscopymentioning
confidence: 99%
“…Medaka (Oryzias latipes) strain i 1 and transgenic line Vg were maintained under an artificial photoperiod of 14-h/10-h light/darkness at 26°C as described [40,45,46]. In medaka, sex maturation occurs until 3 months post hatching.…”
Section: Fishmentioning
confidence: 99%